Association of the Main Phase of the Geomagnetic Storms in Solar Cycles 23 and 24 With Corresponding Solar Wind‐IMF Parameters. Issue 10 (21st October 2022) - Manu, V.; Balan, N.; Zhang, Q.‐H.; Xing, Z.‐Y.
Abstract: The occurrence and intensity of the geomagnetic storms/activity in the weak solar cycle 24 (SC24) were studied mainly for low latitudes, with intensity being the maximum value of the activity. The impulsive strength of the activity giving its mean value during the main phase, which can better indicate the effect of the activity on utility systems, has not received much attention at any latitude. In this paper, we investigate the intensity and impulsive strength of the 179 and 85 clear geomagnetic activities (DstMin ≤ −50 nT) identified in the low, mid and high latitude indices (SymH, Kp, and AE) and corresponding solar wind velocity V, IMF Bz, and the product V × Bz in solar cycles 23–24 (1996–2019) for the first time. Compared to SC23, the total intensity and total impulsive strength in SC24 in all latitudes reduce by nearly equal amounts (∼60%) as the reduction in the number of activities (∼53%). The average intensity and average impulsive strength, however, reduce by nearly equal and largest amounts in low latitudes (∼23%), which is close to the reduction in the combination <−( V × Bz)MP > by ∼30%. At mid and high latitudes, the average intensity and average impulsive strength reduce by only small amounts (∼7.5%). Only the impulsive strength of the geomagnetic activity at low latitudes (IpsSymH) and the combination <−( V × Bz)MP > identify the two power outages happened in SC23. The correlation between IpsSymH and <−( V × Bz)MP > is also high (0.83) in SC23. Plain Language Summary: The geomagnetic activity is known to depend directly on the solar activity that undergoes an 11‐year solar cycle. The last solar cycle 24 (SC24) was the weakest solar cycle in 100 years with a prior long‐deep solar minimum. The occurrence and intensity of the geomagnetic activity in SC24 have been known mainly for low latitudes. The impulsive strength of the activity, which can better indicate its effects on utility systems, has not received much attention at any latitude. In this paper, we investigate the intensity and impulsive strength of the 179 and 85 clear geomagnetic activities (DstMin ≤ −50 nT) identified in the low, mid and high latitude geomagnetic activity indices (SymH, Kp, and AE) and corresponding solar wind velocity V, north‐south component of the interplanetary magnetic field (IMF Bz), and the product ( V × Bz) during the full period of the solar cycles 23 and 24 (1996–2019). The results reveal that the average intensity and average impulsive strength of the geomagnetic activity in SC24 compared to SC23 reduce by nearly equal and largest amounts in low latitudes (21% and 25%) and the reductions are small at mid (∼7.5%) and high (∼6.5%) latitudes. Key Points: The total intensity and total impulsive strength of the geomagnetic activity in solar cycle 24 compared to solar cycle 23 reduce ∼60% each in all latitudes Reductions in the average intensity and impulsive strength are large ∼23% at low latitudes and nearly equal to that in <−( V × Bz)MP > by 30% The correlation coefficient is also highest (0.86) between the low latitude impulsive strength and the combination <−( V × Bz)MP >